DICER1 gene mutations in endocrine tumors. Issue 3 (March 2018) - Solarski, Michael; Rotondo, Fabio; Foulkes, William D; Priest, John R; Syro, Luis V; Butz, Henriett; Cusimano, Michael D; Kovacs, Kalman
Abstract : In this review, the importance of the DICER1 gene in the function of endocrine cells is discussed. There is conclusive evidence that DICER1 mutations play a crucial role in the development, progression, cell proliferation, therapeutic responsiveness and behavior of several endocrine tumors. We review the literature of DICER1 gene mutations in thyroid, parathyroid, pituitary, pineal gland, endocrine pancreas, paragangliomas, medullary, adrenocortical, ovarian and testicular tumors. Although significant progress has been made during the last few years, much more work is needed to fully understand the significance of DICER1 mutations.